BUDAYA KESELAMATAN PASIEN DI RSUD MAJENE - Heriyati, Heriyati; Al-Hijrah, Muhammad Fauzar; Masniati, Masniati (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
The patient safety culture is important because building a patient safety culture is a way to build an overall patient safety program. This study aims to analyze the patient safety culture by analyzing the relationship of communication patterns, incident reporting systems (learning organizations), teamwork, education and training, work climate, leadership commitment, and no blaming culture with a patient safety culture. This study used an analytical survey design with a cross sectional study approach. This research was conducted at the Regional General Hospital of Majene, with a total sample of 226 respondents. Data were analyzed using the Spearman correlation test. The results of the study found a relationship between leadership commitment, teamwork, communication, work climate, no blaming culture, incident reporting, education and training with a culture of patient safety.